2021
DOI: 10.3390/cancers13194746
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Role of GLI/Hedgehog Signaling in Chemoresistance: Implications in Therapeutic Approaches

Abstract: Insight into cancer signaling pathways is vital in the development of new cancer treatments to improve treatment efficacy. A relatively new but essential developmental signaling pathway, namely Hedgehog (Hh), has recently emerged as a major mediator of cancer progression and chemoresistance. The evolutionary conserved Hh signaling pathway requires an in-depth understanding of the paradigm of Hh signaling transduction, which is fundamental to provide the necessary means for the design of novel tools for treatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 166 publications
(210 reference statements)
0
20
0
Order By: Relevance
“…The combination of MK-0752 with dalotuzumab effectively inhibited cell proliferation, angiogenesis, and stem cell propagation in a phase I trial. Likewise, the combination of MK-0752 and docetaxel is used against advanced breast cancer [ 128 ].…”
Section: Pathways Associated With Glioma and Glioblastomamentioning
confidence: 99%
“…The combination of MK-0752 with dalotuzumab effectively inhibited cell proliferation, angiogenesis, and stem cell propagation in a phase I trial. Likewise, the combination of MK-0752 and docetaxel is used against advanced breast cancer [ 128 ].…”
Section: Pathways Associated With Glioma and Glioblastomamentioning
confidence: 99%
“…Studies have also revealed the role of plasticity-mediated drug resistance in cancer cells [83] via the Hh pathway through the upregulation of different proteins like OCT4, BMI 1 and SOX 2, which increased stemness and drug resistance [84]. In studies by Magistri et al and Nguyen et al, it was observed that Smoothened (SMO) inhibition leads to the overexpression of two Hh target genes, GL1 and GL2, which are the transcription factors responsible for the upregulation of the master gene Snail that is known for promoting plasticity in the cancer cells [85].…”
Section: Drug Resistance Mediated By Cancer Cell Plasticitymentioning
confidence: 99%
“…Studies have also revealed the role of plasticity‐mediated drug resistance in cancer cells [83] via the Hh pathway through the upregulation of different proteins like OCT4 , BMI 1 and SOX 2 , which increased stemness and drug resistance [84]. In studies by Magistri et al.…”
Section: Drug Resistance Mediated By Cancer Cell Plasticitymentioning
confidence: 99%
“…Similarly, targeting the Wnt/β-catenin pathway can inhibit CSC self-renewal and metastasis in TNBC [ 40 ]. Inhibition of the Hedgehog pathway reduces CSC frequency and sensitivity to chemotherapy [ 41 ]. Moreover, targeting the TGF-β pathway has been shown to sensitize TNBC cells to chemotherapy and inhibit the EMT process [ 42 ].…”
Section: Signaling Pathways Involved In Cscs Plasticity In Tnbcmentioning
confidence: 99%